Dog man grime and punishment - Pilkey, Dav 1966-; Pilkey, Dav 1966- (New York Scholastic / Graphix, 2020)
"When Dog Man gets fired by the mayor, he needs his friends' help to combat a new threat"--
Ages 7 and Up
Grades 2-3
1 2 23